Применение систем "Азид-металл (полупровоодник)" для регистрации рентгеновского излучения - Макеев М. А. Михаил Алексеевич; Адушев Г. П. Геннадий Павлович; Суровой Э. П. Эдуард Павлович; Кравцов А. В. Анатолий Васильевич (1984, 1984)
Деп. в ОНИИТЭХим, г. Черкассы, 18.09.84, № 919-ХП-84.